Keamanan Pangan Berbasis Kearifan Lokal Semarang DalamPendekatan Komparatif Antropologi Hukum - Emy Handayan; Mas’ut; SuryaKusuma Wardana (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
Food safety for local products is very necessary for people who live in several regions in Indonesia, especially the cityof Semarang. Food safety can be characterized as food that is good, high quality, has quality, guaranteed goodnutrition, safe for consumption. Protection of local food safety in local communities prioritizes food safety and healthof local Semarang residents who consume local food products in Semarang City. So that it can provide legalprotection for local communities, in this case local consumers, so supervision is needed in food policy andstrengthening food institutions. The suggestion used through the Comparative Legal Anthropology approach is thatit is hoped that food safety based on local wisdom can provide legal regulations related to the Food Law which willbe compared with the conditions of society in Semarang City.Keywords: Local Product Food Safety, Local Consumer Protection, Comparative Legal Anthropology